Biotherapeutic potential and mechanisms of action of colchicine. (17th November 2017) - Dubey, Kashyap Kumar; Kumar, Punit; Labrou, Nikolaos E.; Shukla, Pratyoosh
Abstract: Cancer is a clinical situation caused by uncontrolled cell division and is responsible for a large number of deaths worldwide. Colchicine is a classical antimitotic, tubulin-binding agent (TBA) which is being explored for its antitumor activities, although its tubulin-binding ability leads to some toxicity toward normal cells proliferation. Colchicine derivatives are considered as potent antitumor compounds with less toxicity compared to colchicine. Derivatives with substituted functional groups at A-ring (methoxy), B-ring (acetamide) or C-ring (methoxy) have been synthesized via chemical and microbial routes and show modified bioactivities and altered tropolonic functionality. Earlier reports, in combination with our group's research findings, suggest that microbial biotransformation is an efficient choice for the production of bioactive colchicine derivatives. This route has gained significant interest in the mass production of regio-specific, cost-effective, safe and eco-friendly derivatives. The present review paper critically analyzes and discusses the development and application of colchicine derivatives as a potent antitumor molecule and their production through a microbial transformation process. The information provided in this review might assist in the stimulation of new ideas regarding the development of alternative therapeutic agent(s) for cancer treatment.